Interface pressure profile analysis for patellar tendon-bearing socket and hydrostatic socket - Moo, E.K.; Abu Osman, Noor Azuan; Pingguan-Murphy, Belinda; Wan Abas, Wan Abu Bakar; Spence, W.D.; Solomonidis, S.E. (Faculty of Mechanical Engineering, Wroclaw University of Technology, 2009)
Conventionally, patellar tendon-bearing (PTB) sockets, which need high dexterity of prosthetist, are widely used. Lack of chartered and experienced prosthetist has often led to painful experience of wearing prosthesis and this will in turn deter the patients to wear the prosthesis, which will further aggravate stump shrinkage. Thus, the hydrostatic socket which demands relatively lower level of fabricating skill is proposed to replace the PTB socket in order to produce the equivalent, if not better, quality of support to the amputee patients. Both sockets' pressure profiles are studied and compared using finite element analysis (FEA) software. Three-dimensional models of both sockets were developed using MIMICS software. The analysis results showed that hydrostatic socket did exhibit more uniform pressure profiles than that of PTB socket. PTB socket showed pressure concentration near the proximal brim of the socket and also at the distal fibula. It was also found that the pressure magnitude in hydrostatic socket is relatively lower than that of PTB socket.